Romance Scams: Romantic Imagery and Transcranial Direct Current Stimulation - Chuang, Jie-Yu (Frontiers in Psychiatry, 2021)
Love has an enormous effect on mental health. One does not need an actual romantic relationship to be in love. Indeed, romantic love can be built upon without frequent or real-life encounters, such as with a stranger from a matching website. With the advancement of the Internet and the influence of coronavirus disease, it is believed that these distant romantic relationships and related romance scams are burgeoning. Often, the victims of scams keep emotionally attached to the scammer even after the lie is revealed, which is hypothesized to be attributed to the aberrantly exaggerated romantic imagery of the victims. It is observed that many victims suffer from symptoms similar to a posttraumatic stress disorder, and some even consider suicide. However, there is scant literature on this topic. In this article, it is further postulated that the aberrant romantic imagery might be associated with impulsive acts such as suicide once the ideal but fake romantic relationship is dissolved. Thereafter, it is further speculated that manipulation of the visual network, possibly by transcranial direct current stimulation, might be a promising treatment.